Acute fibrinous and organising pneumonia presenting with mass-like imaging: a case report - Wei Zhou; Longyun Zhang; Bin Xu; Chuanhai Wang (Diagnostic Pathology)
Abstract Objective This case report describes a patient with acute fibrinous and organising pneumonia (AFOP) presenting with mass-like imaging on chest computed tomography (CT), aiming to enhance clinical awareness of this rare disease. Case presentation A 66-year-old man presented with cough, sputum, chest tightness and weight loss persisting for 1 month. Chest X-ray revealed a space-occupying lesion in the left lung. Further CT imaging demonstrated irregular soft tissue masses in both the upper and lower lobes of the left lung. Although the imaging findings suggested lung cancer, the final pathological diagnosis confirmed AFOP. The patient was treated with methylprednisolone, resulting in substantial improvement of the upper lobe lesion, whereas the lower lobe lesion showed minimal response. Following the addition of mycophenolate mofetil, the lower lobe lesion decreased substantially. Multiple lung biopsies confirmed the diagnosis of AFOP, with no evidence of a malignant tumour. Conclusions Acute fibrinous and organising pneumonia presents with non-specific imaging findings, and when manifesting as a mass-like lesion, it may be misdiagnosed as lung cancer. Pathological examination remains essential for diagnosis. Close monitoring of the clinical response is crucial during treatment, and the treatment plan should be tailored to individual patient needs.